Terjemah Bahasa Arab Antara Teori dan Praktik - Siti Shalihah (At-Ta'dib, 2017)
Every language is rich with vocabulary and its diversity is consistent with human experience and the development of the culture in which it grows and develops. Every language has its own way in determining the system of symbols and meaning. This will cause the problems in translation. Arabic for example, as the language of Al-Qur'an, has characters structures that different from the Indonesian. It makes the interpreter must know about the process of reconstructing the source language into the target language, because every language has a different way of expressing a similar message. The difference could be at lexical level and grammatical level. From the literature review it can be concluded that basically the process of translation consists of two stages: (1) original textual analysis and understanding of meaning and / or original text message and (2) the revelation of the meaning and message in the target language in words or acceptable sentences in the target language. Differences in the choice of lexical and grammatical forms from one language and other languages makes an interpreter have to be careful in translating. It makes the parallel equivalence of form and meaning is difficult to find in translation.